PERBEDAAN NILAI VO2 MAX ANTARA AKTIVITAS FISIK RENDAH DAN AKTIVITAS FISIK TINGGI PADA LANSIA PENDERITA OSTEOARTHRITIS LUTUT (Lembaga Penerbitan Universitas Esa Unggul, 2016)
AbstractObjective: To determine differences in VO2 max values between low physical activity and high physical activity in elderly patients with osteoarthritis of the knee. Methods: This study is a cross-sectional study to determine VO2 max value differences between low physical activity and high physical activity in elderly patients with osteoarthritis of the knee. The sample consisted of 40 elderly and selected based on purposive sampling technique. Samples were grouped into two groups based on their level of physical activity that lower levels of physical activity group consists of 20 people and the high activity group consisted of 20 people. Measurement of physical activity using the Physical Activity Scale for the Elderly (PASE) and the measurement of VO2 max using the Six Minute Walking Test. Results : The results of the measurement of lower levels of physical activity by using the total sample of 20 people, showed that the mean value for Physical Activity Low PASE is 131.5 with a standard deviation of 7.45160, while for the measurement of VO2 Max showed a mean value of VO2 Max is 18 , 66 with a standard deviation of 0.52661. High Physical Activity measurement results with a sample size of 20 people, showed that the mean value for Physical Activity High PASE is 156.75 with a standard deviation of 8.47209, while for the measurement of VO2 Max showed a mean value for VO2 max was 19.45 with a standard deviation of 0.35019. Normality Test Results obtained by Kolmogorov-Smirnov test of normal data at lower levels of physical activity, VO2 max and abnormal data at high physical activity. On the results using a different test Test Independent Sample T-Test showed the value of p = 0.000, which means there is a difference VO2 max values between low and high physical activity in elderly patients with osteoarthritis of the knee. Conclusion: There is a difference VO2 max value between low physical activity and high physical activity in elderly patients with osteoarthritis of the knee. Keywords: VO2 max, Physical Activity AbstrakTujuan: Untuk mengetahui perbedaan nilai VO2 maks antara aktivitas fisik rendah dan aktivitas fisik tinggi pada lansia penderita osteoarthritis lutut. Metode: Penelitian ini merupakan jenis penelitian cross sectional untuk mengetahui perbedaan nilai VO2 maks antara aktivitas fisik rendah dan aktivitas fisik tinggi pada lansia penderita osteoarthritis lutut. Sampel terdiri dari 40 orang lansia dan dipilih berdasarkan teknik purposive sampling. Sampel dikelompokkan menjadi dua kelompok berdasarkan tingkat aktivitas fisik yaitu kelompok aktivitas fisik rendah terdiri dari 20 orang dan kelompok aktivitas tinggi terdiri dari 20 orang. Pengukuran aktivitas fisik menggunakan Physical Activity Scale for Elderly (PASE) dan pengukuran VO2 maks menggunakan Six Minute Walking Test. Hasil: Hasil pengukuran aktivitas fisik rendah menunjukkan bahwa nilai mean PASE untuk Aktivitas Fisik Rendah adalah 131,5 dengan standar deviasi 7,45160, sedangkan untuk hasil pengukuran VO2 Maks menunjukkan nilai mean untuk VO2 Maks 18,66 dengan standar deviasi 0,52661. Hasil pengukuran Aktivitas Fisik menunjukkan bahwa nilai mean PASE untuk Aktivitas Fisik Tinggi 156,75 dengan standar deviasi 8,47209, sedangkan untuk hasil pengukuran VO2 Maks menunjukkan nilai mean untuk VO2 Maks adalah 19,45 dengan standar deviasi 0,35019. Hasil Uji Normalitas berdasarkan Uji Kolmogorov Smirnov didapatkan data normal pada aktivitas fisik rendah, VO2 maks dan data tidak normal pada aktivitas fisik tinggi. Pada hasil uji beda p = 0,000 yang berarti ada perbedaan nilai VO2 maks antara aktivitas fisik rendah dan tinggi pada lansia penderita osteoarthritis lutut. Kesimpulan: Ada perbedaan nilai VO2 maks antara aktivitas fisik rendah dan aktivitas fisik tinggi pada lansia penderita osteoarthritis lutut. Kata Kunci : VO2 maks, Aktivitas Fisik